Obedience To Compliance Wujud Sikap Positif Wajib Pajak Sistem Coretax Melalui Pendekatan Psikologi Komunikasi - Yeni Nuraeni; Rina Astriani; Sugiharti Binastuti; Ashur Harmadi (Asosiasi Dosen Muda Indonesia, 2026)
Taxation is a crucial instrument for national development; however, its implementation in Indonesia continues to face psychological challenges, particularly when taxpayer adherence is driven more by coercion or fear of sanctions (obedience) than by voluntary awareness (compliance). This study aims to analyze how a psychological communication approach can transform taxpayers’ attitudes from compulsory obedience into voluntary compliance through the implementation of the integrated digital Coretax system. This research employed a descriptive qualitative approach within a constructivist paradigm, drawing on compliance-gaining theory and attitude theory. Data were collected through observation, interviews, and documentation. The findings indicate that the application of five compliance-gaining strategies—rewarding, punishing, expertise, impersonal commitment, and personal commitment—effectively influenced taxpayers’ perceptions and behavior. Positive attitude changes were reflected in cognitive, affective, and behavioral aspects, as shown by taxpayers’ understanding that Coretax is a more accessible and transparent system, reduced fear and anxiety, and the emergence of pride and trust in the state. Behaviorally, account activation increased to 92%, the compliance rate rose to 80.7%, and reporting patterns shifted toward more disciplined and proactive behavior. This study concludes that the success of tax modernization depends not only on technology, but also on persuasive, clear, and psychologically grounded communication. The implication of this study is that the Coretax system can help transform formal tax obligations into moral responsibility and tangible contributions to national development.